Online estimation of inertia and frequency regulation capability based on small perturbation - Wuqi Zhang; Yunfeng Wen; Li Li; Qinglei Zhang; Cheng Cheng; Jun Li (Energy Reports, 2022)
Urged by the low-carbon economic policies, several studies have demonstrated that the vastly available renewable energy sources (RESs) are considered as the promising substitute for the energy-intensive fossil fuel synchronous generators (SGs). This means the power system will operate at low inertia level and frequency regulation capability (FRC), which is provided by conventional SGs. This may weaken the frequency dynamic regulation capability of the system under a contingency transient event. This paper, therefore, develops an inertia and FRC estimation method based on a small sinusoidal active power disturbance. Firstly, utilize the RESs (i.e., energy storage/photovoltaic/wind units and other programable devices) as a sinusoidal active power injected into a power system to obtain the frequency response in frequency domain, namely FR(s). Secondly, analyze the relation between the nodal inertia with SG or RES and the resonance frequency of the amplitude of FR(s), and the relation between the nodal FRC and the dc gain of the amplitude of FR(s), respectively. Based on the deduced relationships, an evaluation framework with the small sinusoidal perturbation for the inertia and FRC estimation is presented. Simulation results demonstrate the effectiveness of the proposed small perturbation-based estimation approach in the modified 9-bus test system. This is useful for the design of the appropriate frequency control strategies for the grid operators and planners.